The Colorado Violent Death Reporting System (COVDRS): Validity and Utility of the Veteran Status Variable - Bahraini, Nazanin H. (Association of Schools of Public Health, 2012)
OBJECTIVE: Using the Veterans Affairs Beneficiary Identification Record Locator Subsystem (BIRLS) as the criterion database, we evaluated the sensitivity and specificity of the death certificate information in the Colorado Violent Death Reporting System (COVDRS) to determine Veteran status for those who died by suicide. METHODS: The study sample consisted of 3,820 individuals aged 18 years and older who died by suicide in Colorado from January 1, 2004, through December 31, 2008. To determine agreement on Veteran status, COVDRS data were submitted to the Veterans Benefits Administration for linkage to the BIRLS using Social Security numbers. RESULTS: Sensitivity and specificity of the Veteran status information on the death certificate were 93.1% (95% confidence interval [CI] 90.7, 95.2) and 91.7% (95% CI 90.5, 92.8), respectively. The overall agreement between the death certificate and the BIRLS on Veteran status was very good (kappa = 0.76; 95% CI 0.74, 0.79). CONCLUSIONS: This study of 3,820 suicide deaths in Colorado demonstrated a high level of agreement between the COVDRS Veteran status variable and the BIRLS. Such findings offer support for using the COVDRS in studying factors associated with suicide in the Veteran population.